Jan Mast, an Utrecht sculptor of funerary monuments in the eighteenth century (Bulletin KNOB, 2006)
Until now, not much was known about Jan Mast, an eighteenth century sculptor from Utrecht. He left four signed funerary monuments in marble, two in the church of Wijhe (province of Overijssel), one in Tiel and one in Houten. Apart from these, a wooden Justice statue by him exists, which is now in the Centraal Museum in Utrecht. Jan Mast is to be regarded as a successor of seventeenth-century sculptors, such as Artus Quellinus, Rombout Verhulst and Bartholomeus Eggers. He often used the same imagery in the mourning symbolism on the funerary monuments. However, in the eighteenth century commissions for such monuments were more frequently given by private individuals than by the authorities as was the case in the seventeenth century. Mast used fashionable elements, such as portrait medallions and a portrait bust, putti and obelisks.From written sources it is known that he also made garden ornaments; unfortunately none of these have been preserved as far as we know. Although the work of Mast lacks the originality of his predecessors, he is still to be regarded as a competent craftsman of his time, when sculptors from the northern Netherlands, particularly in Utrecht did not prevail.